Mixed Convection Boundary Layer Flow Over a Horizontal Circular Cylinder with Newtonian Heating - Mohd Zuki, Salleh; Roslinda, Nazar (Springer-Verlag, 2010)
The steady mixed convection boundary layer flow over a horizontal circular cylinder, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature, is considered in this study. The governing boundary layer equations are first transformed into a system of non-dimensional equations via the non-dimensional variables, and then into non-similar equations before they are solved numerically using a numerical scheme known as the Keller-box method. Numerical solutions are obtained for the skin friction coefficient Re 1/2 C f and the local wall temperature θ w (x) as well as the velocity and temperature profiles with two parameters, namely the mixed convection parameter λ and the Prandtl number Pr.